Indicators of Effectiveness of Removed Dental Prostheses - Navruzova N. O.; Saidov A. A. (Researchparks Publishing, 2021)
The relevance of the topic. Among the reasons for the high need for orthopedic treatment with removable dentures, the leading position is still occupied by